Editorial Ingles - Hernández Suárez, César Augusto (Tecnura, 2011)
Currently, wireless networks and applications in much of the world are characterized by a fixed allocation policy on radio spectrum regulated by the state. This causes fixed assignment of frequencies allocated for specific services are virtually obsolete and cannot be used by unlicensed users, even if they do not introduce any interference. (Akyildiz I., Lee, Vuran, & Mohanty, 2008).